Education meets Art: Political-Pedagogical notes on Rights and Early Childhood Education - Sandra Regina Simonis Richter; Adriana Alves da Silva; Ana Lúcia Goulart de Faria (Universidade Federal de Santa Catarina, 2017)
In order to problematize the tendency of imposing in preschools (and very often in day care centers) a pedagogy based on the school logic, rooted in the sciences of regularity, focused on the analytical teaching, centered on the teacher and knowledge transmission, we propose an interlocution between art, education and the very earliest childhood. The encounter between art and childhood fosters the discussion about the gaps in the teacher's formation, who is always among young children, mainly the tiny young ones, to educate them way beyond their prevailing cognitivism. From philosophers and thinkers interested in life and its unfoldings, we approach the poetic imagination, the joy and the complexity of learning, the right to beauty and the language experience that emerges from the sensitive body to raise the political urgency for another Childhood Pedagogy. The experience of the sensitive and linguistical body in its first learning summons a pedagogy which does not segregate experience from knowledge, body from mind, thought from action in the world. This inseparability allows one not only to resist the exclusively scientific bases of Pedagogy and its structural technicality - the didactics -  but also to assess the relevancy of art in the teaching formation and its power to agglutinate poetic, political and pedagogical meetings that guarantee full rights to childhood and education.